Analisis Pengaruh Variasi Penempatan Dinding Geser Terhadap Perilaku Struktur Gedung Akibat Beban Gempa - Irfan Hidayatullah; Eko Walujodjati (Jurnal Konstruksi, 2025)
Indonesia is located in the Pacific Ring of Fire, so it has many active faults that increase the risk of earthquakes, including in Tasikmalaya. To reduce damage to buildings caused by earthquakes, earthquake-resistant structural planning is required, one of which is the use of shear walls. This study aims to analyze the effect of varying shear wall placements on base shear forces, inter-story drifts, and P-Delta effects. The analysis was performed numerically using ETABS (Student Version) software with the response spectrum method based on SNI 1726:2019. Three shear wall placement models were used: model 1 according to existing conditions, model 2 in the middle of the building, and model 3 at the corner of the building. The analysis results show that model 2 provides the best response. The base shear force reached 1,422.6 kN, the inter-story drift was 7.49 mm in the X direction and 5.46 mm in the Y direction, remaining below the maximum limit. The P-Delta effect in model 2 was also the lowest and most consistent, with a maximum value of 0.0031 in the X direction and 0.0022 in the Y direction. Therefore, placing shear walls in the center of the building was most effective in improving the structure's performance against seismic loads. These findings can provide practical input for structural designers in determining the placement strategy for shear walls in multi-story buildings in earthquake-prone areas.